DEPICTION OF THE HISTORY OF FERGHANA IN THE EARLY MEDIEVAL PERIOD IN “NASABNOMA” (Scientific journal of the Fergana State University, 2023)
The history of Ferghana valley of pre-Islamic period was studied by written sources and archeological materials. Particularly, a number of researchers mentioned the local ruling dynasties and administration matters of Turkic Khaganate in Early Medieval Ferghana valley. Furthermore, several researches about political events that occurred in the eve of Arab invasion, struggle against Arab invaders and other events were conducted, but they cannot be considered as “perfect sources”. “Nasabnoma” that has been recently presented to the scientific world, is playing a great role in the study of this issues about local dynasties that ruled over the Ferghana valley in pre-Islamic period.